2022
DOI: 10.1177/15248380221126184
|View full text |Cite
|
Sign up to set email alerts
|

Trauma and Substance Use among Indigenous Peoples of the United States and Canada: A Scoping Review

Abstract: Substance use has been identified by Indigenous populations as contributing to health disparities facing their communities. Rates of trauma exposure and post-traumatic stress disorder are higher in Indigenous, compared to non-Indigenous, populations and have been linked to substance use. Historical trauma is thought to be one mechanism underlying substance use and related disorders. The purpose of the present study is to summarize the current state of the literature focusing on the association between trauma (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 111 publications
1
1
0
Order By: Relevance
“…These observations are consistent with empirical findings, with one recent scoping review finding that 86.4% of studies found evidence for a positive link between alcohol and other drug use and historical trauma (Spillane et al, 2022). For instance, the findings of Whitbeck et al (2004) showed that higher levels of historical loss predicted an increased likelihood of alcohol use disorder among American Indians.…”
Section: Discussionsupporting
confidence: 87%
“…These observations are consistent with empirical findings, with one recent scoping review finding that 86.4% of studies found evidence for a positive link between alcohol and other drug use and historical trauma (Spillane et al, 2022). For instance, the findings of Whitbeck et al (2004) showed that higher levels of historical loss predicted an increased likelihood of alcohol use disorder among American Indians.…”
Section: Discussionsupporting
confidence: 87%
“…We did not examine the prevalence among Sami and non-Sami specifically. However, Table 2 indicates that more Sami than non-Sami participants report emotional abuse in childhood, which corresponds to other research on indigenous populations [ 16 19 ]. There might be several possible explanations for this trend, but harsh assimilation policies, colonization and discrimination appear to be the main hypotheses [ 21 , 50 ].…”
Section: Discussionsupporting
confidence: 82%
“…Research on childhood abuse in indigenous populations is based on limited data. However, some research has indicated that childhood violence is more common among indigenous than non-indigenous populations [16][17][18][19]. This has been linked to the cultural experience the indigenous populations have had to endure, such as harsh assimilation policies, colonization, and discrimination [16,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…However, many core components of IRP, if adapted, may be transferable to other communities. Although each tribe has a unique history and culture, there are commonalities among many AI/AN cultural groups, including the history of colonization that gave rise to historical trauma and disproportionately high rates of SUD (Nutton & Fast, 2015;Pride et al, 2021;Spillane et al, 2022), inadequate funding of the Indian Health Service ( Joseph et al, 2019;Whitesell et al, 2012), and a preference for culturally grounded interventions (Walters et al, 2020;Wendt et al, 2022). Many Native cultures share common values regarding the importance of family, language, spirituality, and cultural identity (Dickerson et al, 2020;Walters et al, 2020) and may find elements of IRP to be well-suited to their communities.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%